Análise de viabilidade em adicionar proteção à privacidade na camada de aplicação em redes smart home - Trindade, Fernando Henrique Vieira (2022)
Smart Home is one of the fastest-growing emerging technologies over the years.In order to provide communication to smart objects, it is necessary to use "light" communication protocols so as not to overload them. Due to limited hardware resources in SHS (Smart Home System), requirements such as response time, low processing load, and low power consumption are often prioritized over security and privacy. However, in this type of environment, data traffic in an insecure way exposes the privacy and intimacy of users. After reviewing the literature, it was identified that applications using the MQTT and CoAP protocols (two of the main application layer protocols) were developed in an insecure way. Therefore, these protocols were chosen to be analyzed regarding security mechanisms and their impacts on domestic use. This dissertation applies statistical methods in experiments with MQTT and CoAP protocols, using the ESP32 microcontroller, and measures the impact of adding authenticity and confidentiality to the application layer in SHS in terms of performance, energy efficiency, and usability.Tests of sending and receiving messages without using any privacy protection were performed and then compared with new tests using TLS for MQTT and DTLS for CoAP. In addition to the increase in security, levels of reliability and expansion of the payload size were also added. For each of these scenarios, the cost of energy consumption, the response time between sending and receiving the message, as well as the complexity required to add the TLS and DTLS protocols to protect the MQTT and CoAP respectively, were evaluated. The results obtained show that the value (in Brazilian Real currency) of energy consumption increased by 2 cents for CoAP with DTLS and 7 cents in the most secure scenario using MQTT with QoS2 + TLS and the 1kb payload. The level of complexity increased from 4 points to 24 using the heuristic evaluation developed in this work. As for the performance in MQTT an overhead of up to 1500% and in CoAP of 178% was identified in the tests with greater security and reliability. Although the numbers seem expressive, given the impact of the lack of privacy, the results showed that the use of TLS and DLTS security protocols are feasible in the smart home environment.